The Contribution of Sex, Personality Traits, Age of Onset and Disorder Duration to Behavioral Addictions - Valero-Solís, Susana; Granero, Roser; Fernández-Aranda, Fernando; Steward, Trevor; Mestre-Bach, Gemma; Mallorquí-Bagué, Núria; Martín-Romera, Virginia; Aymamí, Neus; Gómez-Peña, Mónica; del Pino-Gutiérrez, Amparo; Baño, Marta; Moragas, Laura; et al. (Frontiers in Psychiatry, 2018)
Background and aims: Increases in the prevalence of behavioral addictions worldwide have led to a growth in the etiological research of the specific contribution of risk/protective factors to these disorders. The objective of this study was to assess the relative role of patients’ sex, age of disorder onset and disorder duration on the clinical profile of behavioral addictions. Methods: Our sample included treatment-seeking patients diagnosed with gambling disorder (GD, n=3,174), internet gambling disorder (IGD, n=45), compulsive buying (CB, n=113) and sex addiction (SA, n=34). Results: The pattern of associations between the independent variables and the outcomes were strongly related to the behavioral addiction subtype: a) for GD-men early onset of the disorder was related to GD severity, while for GD-women early onset was linked to novelty seeking; b) for IGD-men, late onset correlated with addiction severity , worse psychopathological state, and high harm avoidance and self-transcendence levels; c) for CB-women, early onset was related to higher reward-dependence scores and lower self-transcendence levels, and longer duration predicted higher cumulate debts; for CB-men, early onset and long duration correlated with high scores in harm-avoidance, self-directedness, self-transcendence and cooperativeness; and d) for SA-men, late onset and longer duration correlated with high disorder severity. Discussion and Conclusions: These findings are relevant for developing prevention and treatment programs specific to different behavioral addictions.